Effectiveness of Group Therapy Based on Acceptance and Commitment on the Severity of Fatigue and Depression with the Moderating role of Alexithymia in Multiple Sclerosis Patients - Haji Seyed Javadi, Tahereh; Aghel Masjedi, Maryam; Hamzehloo, Elnaz; Chehraghi, Mir Javad; Razavi, Leila; Rahmani, Soheila; Nejati, Somayeh (International Clinical Neuroscience Journal, 2020)
Objective: Alexithymia is a symptom that most psychosomatic patients experience and can affect their performance, psychological state, and the severity of their physical symptoms. Therefore, the present study was conducted to determine the effectiveness of group therapy based on acceptance and commitment on the severity of fatigue and depression with the moderating role of alexithymia in MS patients in Tehran. Methodology: In this research, a semi-experimental design was used with pre-test, post-test, and three months of follow-up. Using convenience sampling, 40 patients with MS were randomly assigned to two experimental and control groups. Before and after the intervention and three months later in the follow-up phase, all of the subjects responded to fatigue severity, depression, and alexithymia questionnaires. The intervention consisted of 10 sessions of 90-minutes group therapy based on acceptance and commitment, which was provided only to the experimental group. Findings: Analysis of covariance indicated a significant difference between the mean scores of fatigue severity, depression, and alexithymia in the experimental and control groups in post-test and follow-up stages. Conclusion: The findings of this study indicated the effectiveness of group therapy based on acceptance and commitment on reducing the severity of fatigue and depression with the moderating role of alexithymia in MS patients.